Workshop Mampu Meningkatkan Kompetensi Guru dalam Implementasi Blended Learning - Karsiyem Karsiyem (Ideguru: Jurnal Karya Ilmiah Guru, 2023)
Limited Face-to-Face Learning (LFFL) requires teachers to increase learning creativity and innovation. Workshop activities are an alternative to overcome this. This writing aims to provide an illustration that workshops can improve the ability to implement blended learning in Cluster I Pengasih, Kulon Progo Regency, for the 2021/2022 academic year. School Action Research (PTS) which was carried out in two cycles. The research subjects were 8 grade 4 teachers. The research data was obtained through observation/observation of the planning and implementation of learning. The results of each cycle were analyzed using a descriptive percentage analysis, then used as a reference for the next action. An indicator of the success of teacher competence in implementing blended learning is when the percentage of teachers and the component indicators of blended learning implementation in the good category has reached 75%. The results showed that the teacher's ability to implement blended learning increased in workshop preparation from 85 (Good) to 94 (Very Good), Workshop implementation for resource persons increased from 80 (Good) to 94 (Very Good), Workshop implementation from participant observations increased from 85 (Good) to 91 (Very Good), preparation of lesson plans increased from 89 (Good) to 94 (Very Good), offline learning increased from 90 (Good) to 94 (Very Good), and online learning increased from 91 (Very Good) Good) to 94 (Very Good). In addition to workshops, competency in implementing blended learning can be developed through offline/online learning communities at the school, cluster, sub-district and district levels.